Electronic, optical and thermoelectric properties of BN-Be(8, 0) nanotube: DFT study. (15th September 2022) - Sotudeh, Mina; Boochani, Arash; Parhizgar, Sara Sadat; Masharian, Seyedeh Razieh
Abstract: Based on density functional theory calculations, the electronic, optical and thermoelectric properties of pure BN(8, 0) nanotube and under Be impurity are discussed. The BN(8, 0) nanotube is a pure non-magnetic semiconductor with an energy gap of 3.66 eV along the Γ direction. Still, in the presence of the Be impurity, in BN(8, 0) nanotube, we see magnetic asymmetry at its Fermi level, resulting in the BN-Be(8, 0) nanotube compound having a half-metallic behavior. The real and imaginary parts of dielectric functions confirm the electronic properties so that in the imaginary part of the dielectric function in both optical directions x, z, in the pure phase, we see a gap of 4 eV, and in the impure form, the gap is about is zero. At energies above 5eV, the real part of the dielectric function is less than one, which represents the super luminescence behavior. Thermoelectric properties show that the effect of Seebeck at room temperature is significant in spin-up and increases with increasing temperature with a positive slope. Also, the merit and power factor coefficients increase at higher temperatures, which indicates the behavior of the power generator. Highlights: The BN-Be (8, 0) nanotube has half-metallic behavior with 1μB magnetic moment. The BN-Be (8, 0) nanotube has intraband transition at lower energies. The Seebeck of BN-Be (8, 0) nanotube increased at high temperatures.